Idiopathic Sclerosing Encapsulating Peritonitis in a Patient with Atypical Symptoms and Imaging Findings - Joseph Wetherell; Katherine Woolley; Rishi Chadha; Julia Kostka; Edin Adilovic; Pankaj Nepal (Case Reports in Gastrointestinal Medicine)
Sclerosing encapsulating peritonitis is a rare condition caused by a fibrotic membrane covering the small bowel which may lead to abdominal pain or obstruction. The cause may be primary and idiopathic or secondary to several diseases, treatments, and/or medications. The condition typically presents with bowel obstruction, and only one previous case has described ascites as the presenting sign. Sclerosing encapsulating peritonitis is typically diagnosed intraoperatively. We present a case of a patient who presented with atypical clinical symptoms including respiratory distress, recurrent abdominal ascites, and failure to thrive who was diagnosed nonoperatively.